2015
DOI: 10.1016/j.jnucmat.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Fast, quantitative, and nondestructive evaluation of hydrided LWR fuel cladding by small angle incoherent neutron scattering of hydrogen

Abstract: a b s t r a c tA nondestructive neutron scattering method to precisely measure the uptake of hydrogen and the distribution of hydride precipitates in light water reactor (LWR) fuel cladding was developed. Zircaloy-4 cladding used in commercial LWRs was used to produce hydrided specimens. The hydriding apparatus consists of a closed stainless-steel vessel that contains Zr alloy specimens and hydrogen gas. Following hydrogen charging, the hydrogen content of the hydrided specimens was measured using the vacuum h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…1). The crystal orientation mapping by electron backscatter diffraction (EBSD) reveals that our samples are heavily textured (Yan et al, 2014), which might result in the circumferential hydrides, as shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…1). The crystal orientation mapping by electron backscatter diffraction (EBSD) reveals that our samples are heavily textured (Yan et al, 2014), which might result in the circumferential hydrides, as shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 96%
“…This naturally high sensitivity of hydrogen through neutron scattering techniques allows for a detailed, non-destructive study of zirconium cladding. Neutron radiography and scattering have been used to study the hydrogen distribution (Brosse et al, 2006, Lehmann et al, 2004, Yan et al, 2014, Yasuda et al, 2003, by which hydrogen content higher than a few hundred ppm can be quantitatively detected using the property of neutron attenuation due to absorption and scattering from hydrogen. This work shows that neutron radiography and tomography can be used for hydrogen analysis of hydrided Zircaloy-4 cladding samples with a wide range of hydrogen concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the thin coating, the mechanical behavior after oxidation is rooted in the reduced oxidation and potentially reduced hydrogen pickup instead of an increased circumferential thickness. The hydriding system consists of a tube furnace with a stainless steel tube that is heated to high temperatures in the presence of hydrogen to introduce a desired quantity of hydrogen into the specimen [14]. Hydrogen uptake at elevated temperature results in the formation of hydrides, which are stable when cooled to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The hydriding temperature was set to 425 °C, and the initial tube pressure was varied to adjust to the specimen's target hydrogen concentrations. The hydrogen content of the hydrided specimens was measured using the inert gas fusion technique per ASTM E1447-05 or the The hydriding system consists of a tube furnace with a stainless steel tube that is heated to high temperatures in the presence of hydrogen to introduce a desired quantity of hydrogen into the specimen [14]. Hydrogen uptake at elevated temperature results in the formation of hydrides, which are stable when cooled to room temperature.…”
Section: Methodsmentioning
confidence: 99%